PENGARUH INFLUENCER MARKETING, CONTENT MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PADA BRAND KOSMETIK MAKE OVER - Salim, Devanya Azzura Andini; Yusrin, Nur Amalyna (Jurnal Nusa Manajemen, 2025)
The advancement of information technology, particularly the growth of e-commerce in Indonesia, has created intense competition across various business sectors, including the cosmetics industry, which has become one of the most promising sectors. This study aims to analyze the influence of influencer marketing, content marketing, and online customer reviews on purchase intention among consumers of the Make Over cosmetic brand in the Greater Jakarta area (Jabodetabek). The research adopts a quantitative approach using a non-probability sampling technique. Data were collected through an online questionnaire (Google Form), resulting in 235 respondents. The data analysis technique employed was Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.1 software. The findings indicate that influencer marketing, content marketing, and online customer reviews simultaneously have a significant effect on purchase intention. Specifically, influencer marketing strategies were found to be the primary factor influencing consumers' purchase intentions for Make Over products. These findings are expected to provide valuable insights for Make Over in enhancing the effectiveness of their marketing strategies, enabling them to drive purchase intentions through influencer marketing, content marketing, and credible online customer reviews.